2014
DOI: 10.1007/s00592-014-0568-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-dipping and arterial hypertension depend on clinical factors rather than on genetic variability of ACE and RGS2 genes in patients with type 1 diabetes

Abstract: The aim of our study was to characterize the association of clinical and genetic risk factors such as: ACE genotype (rs17997552, rs1800764, rs4459609) and RGS2 (rs2746071) with the development of hypertension (HT) and non-dipping phenomenon in patients with type 1 diabetes mellitus (T1DM). A total of 238 adolescents and young adults with T1DM—103 females and 135 males, aged 8–30 years (mean 17.35 ± 5.2) with diabetes duration 1–26 years (mean 7.72 ± 6.2), with mean HbA1c (IFCC) 58 ± 15 mmol/mmol—were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Thus, abnormal signaling pathways in the kidney of RGS2 À/À mice could impair water and solute processing. The authors of the original study of the hypertension of RGS2 À/À mice hypothesized that the differential acute changes in blood pressure between WT and RGS2-deficient mice to vasoconstrictor antagonists argued against plasma volume changes in RGS2 À/À mice as the primary cause of hypertension (Deja et al, 2014;Gurley et al, 2010;Heximer et al, 2003;Kvehaugen et al, 2014Kvehaugen et al, , 2013Nance et al, 2013;Zhang et al, 2013). One study has shown no difference in renal sympathetic activity in WT or RGS2 À/À mice (Tank et al, 2007).…”
Section: Rgs2mentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, abnormal signaling pathways in the kidney of RGS2 À/À mice could impair water and solute processing. The authors of the original study of the hypertension of RGS2 À/À mice hypothesized that the differential acute changes in blood pressure between WT and RGS2-deficient mice to vasoconstrictor antagonists argued against plasma volume changes in RGS2 À/À mice as the primary cause of hypertension (Deja et al, 2014;Gurley et al, 2010;Heximer et al, 2003;Kvehaugen et al, 2014Kvehaugen et al, , 2013Nance et al, 2013;Zhang et al, 2013). One study has shown no difference in renal sympathetic activity in WT or RGS2 À/À mice (Tank et al, 2007).…”
Section: Rgs2mentioning
confidence: 94%
“…One study has shown no difference in renal sympathetic activity in WT or RGS2 À/À mice (Tank et al, 2007). Although the significance of the renal abnormalities in the absence of RGS2 for regulation of plasma volume and systemic blood pressure is far from clear, its role in renal water and salt handling has been intensively studied with genetic correlations between RGS2 and the association of hypertension in humans (Deja et al, 2014;Kvehaugen et al, 2014Kvehaugen et al, , 2013Nance et al, 2013;Osei-Owusu et al, 2012;Sjogren et al, 2012;Zhang et al, 2013). Third, RGS2 exerts control over vascular tone through an interaction with a component of the nitric oxide (NO) pathway, protein kinase G (PKG)/cGMP-dependent protein kinase, which influences vascular relaxation mediated by NO (discussed in detail below) (Sun et al, 2005;Tang et al, 2003).…”
Section: Rgs2mentioning
confidence: 99%
“…Nondipper hypertension is frequently accompanied by endothelial dysfunction and activation [40,41]. Type 1 diabetic patients who did not display dipping showed a two-fold increase in risk of developing hypertension [42]. Among patients with postural tachycardia syndrome, a nondipping BP profile is associated with a reduced orthostatic sympathetic reactivity not accounted for by autonomic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the ACE I/D polymorphism had no influence on ND, which corroborates the results of other authors [ 21 , 23 ] although one study demonstrated a smaller drop between awake and sleep BP in hypertensive patients with the DD genotype in comparison to carriers of the I allele [ 44 ]. In addition, there was no effect of ACE I/D polymorphism or serum ACE levels on circadian variability of blood pressures among pediatric renal transplant patients [ 46 ] and in patients with type 1 diabetes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%